GAMBARAN KLINIS PASIEN APENDISITIS AKUT DENGAN MENGGUNAKAN PENILAIAN TZANAKIS SKOR DAN ALVARADO SKOR DI RSUD DR H ABDUL MOELOEK BANDAR LAMPUNG TAHUN 2014 - Andi Siswandi (Jurnal Medika Malahayati, 2015)
The incidence of appendicitis in Hospital Dr. H. Abdul Moeloek Bandar Lampung in 2014 each month, including 10common diseases. New problems arise when the lower right abdominal tenderness not ensure appendicitis. The purpose ofthis study was to determine the clinical features of acute appendicitis patients using Tzanakis assessment score andAlvarado score in the Hospital Dr. H. Abdul Moeloek Bandar Lampung in 2014.This type of research is descriptive retrospective study using medical records. The population is all appendicitispatient data in the inpatient surgical Rose and Kutilang Hospital Dr. H. Abdul Moeloek Bandar Lampung In 2014 as many as94 people. Data analysis using univariate analysis using the table in the presentation of the data.Results of the study there were 76 patients who met the criteria for inclusion in the study. Of the 76 patients wereobtained clinical picture of acute appendicitis based Tzanakis scores namely ultrasound (60.53%), pain in the right lowerquadrant (100%), off the right lower quadrant pain (40.79%), and leukocytes> 12.000mm3 (52.63%). Alvarado scoresnamely pain shifts in the lower right quadrant (11.84%), anorexia (86.84%), nausea and vomiting (48.68%), pain in the rightlower quadrant (100%), pain in the right lower quadrant off (40.79%), raising the temperature of 37.5 ° C-38 ° C (30.26%),leukocytosis (68.42%), white blood cells shift to the left (65.79%).